2008
DOI: 10.1038/ng.2007.65
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in mRNA export mediator GLE1 result in a fetal motoneuron disease

Abstract: The most severe forms of motoneuron disease manifest in utero are characterized by marked atrophy of spinal cord motoneurons and fetal immobility. Here, we report that the defective gene underlying lethal motoneuron syndrome LCCS1 is the mRNA export mediator GLE1. Our finding of mutated GLE1 exposes a common pathway connecting the genes implicated in LCCS1, LCCS2 and LCCS3 and elucidates mRNA processing as a critical molecular mechanism in motoneuron development and maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
190
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(193 citation statements)
references
References 15 publications
0
190
3
Order By: Relevance
“…Mutations in various RNA-binding proteins, such as SMN, TARDBP, FUS and GLE1 have been identified as genetic causes of motor neuron degeneration (Lefebvre et al, 1995, Sreedharan et al, 2008, Nousiainen et al, 2008, Vance et al, 2009. The GLE1 gene is mutated in LCCS1, a severe autosomal recessive fetal motor neuron disease (Nousiainen et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mutations in various RNA-binding proteins, such as SMN, TARDBP, FUS and GLE1 have been identified as genetic causes of motor neuron degeneration (Lefebvre et al, 1995, Sreedharan et al, 2008, Nousiainen et al, 2008, Vance et al, 2009. The GLE1 gene is mutated in LCCS1, a severe autosomal recessive fetal motor neuron disease (Nousiainen et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms include hypolasia, pytergia, multiple joint contractures and micrognathia. Prenatal death usually occurs before the 32 nd gestation week (Nousiainen et al, 2008 ). More recently, it has been suggested that haploinsufficieny for GLE1 may be a genetic factor predisposing to ALS (Kaneb et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in patients with osteogenesis imperfecta type I, a splice site mutation causes the entrapment of the COL1A1 (collagen type 1, alpha 1) pre-mRNA in the nucleus, which prevents translation in the cytoplasm (Johnson et al, 2000). Moreover, mutations in the mRNA export factor GLE1 are responsible for motor neuron diseases, LCCS1 (lethal congenital contracture syndrome 1) and LAAHD (lethal arthrogryposis with anterior horn cell disease) (Nousiainen et al, 2008).…”
mentioning
confidence: 99%